A Review of Challenges to Applying Information and Communication Technology in English Language Instruction - Erwin Pohan; Didi Suherdi; Pupung Purnawarman (English Department - University of Sultan Ageng Tirtayasa, 2023)
This research aimed to review the literature on teachers' low interest in employing digital tools in their teaching practices. There were 34 pieces of research, and the issues associated with using it in English language training were found. The problems were explored with a systematic review. The results revealed that most teachers had poor confidence, inadequate training, and insufficient time using technology tools in their classrooms. A summary of the argumentation was presented alongside the paper. Then, Preferred Reporting Items for Systematic and Meta-analysis (PRISMA) statements with four stages: identification, screening, eligibility, and included were conducted to certify the review processes. Moreover, the findings suggested that administrations provide teachers with adequate training and time to successfully utilize technology apparatus in English classroom practices by reducing the teachers' workload. Additionally, the teachers could manage, organize their time and skills, and participate in personal online training to solve their problems and improve their capacity to practice technology tools in the classroom.